A league-wide investigation into variability of rugby league match running from 322 Super League games. Issue 3 (3rd July 2021) - Dalton-Barron, Nicholas; Palczewska, Anna; McLaren, Shaun J.; Rennie, Gordon; Beggs, Clive; Roe, Gregory; Jones, Ben
ABSTRACT: Purpose: This study investigated sources of variability in the overall and phase-specific running match characteristics in elite rugby league. Methods: Microtechnology data were collected from 11 Super League (SL) teams, across 322 competitive matches within the 2018 and 2019 seasons. Total distance, high-speed running (HSR) distance (>5.5 m·s −1 ), average speed, and average acceleration were assessed. Variability was determined using linear mixed models, with random intercepts specified for player, position, match, and club. Results: Large within-player coefficients of variation (CV) were found across whole match, ball-in-play, attack and defence for total distance (CV range = 24% to 35%) and HSR distance (37% to 96%), whereas small to moderate CVs (≤10%) were found for average speed and average acceleration. Similarly, there was higher between-player, -position, and -match variability in total distance and HSR distance when compared with average speed and average acceleration across all periods. All metrics were stable between-teams (≤5%), except HSR distance (16% to 18%). The transition period displayed the largest variability of all phases, especially for distance (up to 42%) and HSR distance (up to 165%). Conclusion: Absolute measures of displacement display large within-player and between-player, -position, and -match variability, yet average acceleration and average speed remain relatively stable across all match-periods.